Implementation of Multifunction Residue Architectures on FPGA for Cryptography Applications: A Recent Study - A. Pradeep Kumar; V. Srinivas (Novel Perspectives of Engineering Research Vol. 3, 2021)
Confidentiality and encryption of data are critical features of modern computing. Elliptical curve cryptography (ECC) is the ultimate cryptographic method due to its high limited size and thus its reliability equal to that of other traditional public-key algorithms. Furthermore, hardware acceleration of cryptographic algorithms is required to meet the increasing speed demand for contemporary implementations. The forward converters, modulo decimal units, and reverse converters are the core components of the residue number method. In the current network of residue numbers, the reverse converter is based on standard and compact adders. It has a high power consumption and a low speed. By analysing the input/output conversion to/from residue representation, it proposed a residue Montgomery method for multiplying data pathways among converters and between the two residue representations. The dual field modulator is used for GF(p) and GF(2)n Montgomery multiplication, input/output conversions, mixed-radius conversions (MRC) for inputs and polynomials, and exponentiation and inversion in the same hardware.